Industrial Furnaces in Problem of Nitrogen Oxide Emission Reduction - B. S. Soroka (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper analyzes methods of reducing nitrogen oxide emission in industrial furnace combustion products. Special attention is given to techniques of emission reduction while organizing low-emission fuel combustion. The paper reveals a possibility to monitor NO2 formation mechanism while using a two-stage fuel combustion in comparison with concentrated one-stage combustion. Principal schemes of two-stage combustion with application of various gas burners are given in the paper.